Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

The complex case for another hard look : transnational pharmaceutical regulation and the pedagogical role of courts - Rizzi, Marco (European University Institute, 2015)
The thesis argues for a 'pedagogical' role for courts in the US and EU in ameliorating the increasingly transnational regulation of pharmaceutical product safety through complementary monitoring of the outputs of regulatory processes. The study is divided into two parts. First, the thesis explores the regulatory institutional design in the US and EU. The parallel development of the FDA and EMA suggests that both markets have achieved consolidated domestic/regional regulatory frameworks, which do however show multiple weak spots. These vulnerabilities are aggravated by a strong push towards transnationalisation of regulatory procedures: domestic systems are now permeated by potentially disruptive exogenous elements (e.g. the ratification of transnationally negotiated protocols and increasing reliance on foreign clinical trials data). The thesis explores issues of effectiveness of safety delivery and legitimacy of rule-making processes to suggest scope for improvement in both areas. The second part considers the potential contribution of the judiciary, particularly national courts in the US and EU, to investigate whether the exercise of complementary judicial governance can enhance the effectiveness and legitimacy of an otherwise essentially closed and self-perpetuating system. A selection of cases grounds the claim that, through liability litigation, courts have the capacity to improve the safety levels delivered by regulation and thereby to contribute to output-based legitimacy of the institutional design. This claim is tested in light of acknowledged strengths and limitations of court processes and with regard to differentiating elements at the national level, particularly regarding access to justice. The concluding argument reassembles the results of the study to recommend the existing tool of domestic litigation as a response to certain vulnerabilities in pharmaceutical regulation. The 'hard look' doctrine described by Sheila Jasanoff grounds the normative claim for a 'pedagogical' role for courts, enhancing regulation beyond the outcome of isolated cases – ad adiuvandum rather than contra.
Accepted: 2015-11-04T16:35:28Z
Keywords: Drugs; European Union countries; Pharmaceutical industry; Pharmaceutical regulation; Pharmaceutical right; United States

Public-private cooperation in transnational regulation - Schmidt, Rebecca (European University Institute, 2015)
This thesis examines the emergence of transnational regulatory cooperation between public and private actors. It inquires why a private regulator and an international organisation may enter into a cooperation agreement in order to regulate particular issues, and what this tells us about the relationship between ‘expertise,’ ‘authority’ and ‘legitimacy’ in particular domains of global governance. The argument put forward in the thesis is that different types of regulators cooperate because, in an unsettled global space with no hierarchical framework, it is necessary for them to acquire sufficient authority to secure compliance with their regulatory agenda. In order to acquire and maintain such authority, regulators must be perceived as legitimate and their regulation as effective. Cooperation can open venues for participation and deliberation and for the exchange of necessary competences (particularly expertise); and thus ultimately can help regulators establish and strengthen their authority. Another important finding of this research is that cooperation can develop into more long-lasting network structures. These networks are often of a multi-level nature. As such, they traverse local, national, and international spaces. The thesis then develops the idea of ‘networks of constitutionalization’ to describe the observation that bilateral arrangements as examined here generate ordering effects which extend beyond the two parties. Consequently they become the basis for norm creation and adoption for different types of actors located in the networks formed around the issue area. Thus, even in pluralistic structures, eventually a certain kind of constitutionalization can emerge putting into question sharp divisions between ‘pluralist’ and ‘constitutionalist’ interpretations of a developing global (legal) order. This work also encompasses two case studies: the ISO 26000 process, whereby the ‘private’ technical standard setter ISO concluded separate cooperation agreements with the ILO, the OECD and the UN Global Compact; and a case study on ‘Sport and Environment’ that focuses on the long-standing cooperation between the IOC and the UN Environmental Programme.
Accepted: 2015-04-16T14:24:52Z
Keywords: International Law; Law and Globalization